Decision-Making in Clival Mass Lesions: Risk Factors for Malignant Disease and an Illustrative Case Example - Baier, Matthew P.; Cheong, Daniel A.; Shi, Helen H.; Peterson, Jo Elle G.; Fung, Kar-Ming; Dunn, Ian F.; McKinney, Kibwei A.; Graffeo, Christopher S. (Journal of Neurological Surgery Reports, 2023)
Introduction Clival tumors are rare and heterogeneous. Although some benign prototypical sellar lesions may present as clival tumors, the likelihood of malignant disease is higher. Here we define a novel algorithm for the workup and management of clival masses through an illustrative case of colorectal adenocarcinoma metastasis to the clivus.Methods In this case report, the best practice guidelines for managing clival masses are described through a literature review and refined by senior author consensus. We conducted a focused systematic review to characterize the present case in the context of clival metastasis from gastrointestinal malignancy.Results An 83-year-old woman presented with 4 weeks of headaches and blurry vision. Examination revealed partial right abducens and left oculomotor palsies. Magnetic resonance imaging (MRI) identified a large, weakly enhancing sellar and clival mass with sphenoid sinus extension. An aggressive subtotal endoscopic endonasal resection was performed with removal of all sphenoid, clival, and sellar disease without cavernous sinus wall resection. Pathology confirmed colorectal adenocarcinoma; computed tomography (CT) imaging identified an ascending colon mass with metastases to the liver and mesenteric nodes. Palliative oncologic therapies were recommended, but she elected hospice, and died 3 months after initial presentation. Gastrointestinal clival metastases are exceedingly rare among sellar and clival pathologies, with eight prior cases reported, most of which presented with diplopia from abducens nerve involvement.Conclusion Clival masses are uncommon skull base lesions that are associated with more aggressive diseases. We present a consolidated framework for decision-making in these challenging patients, alongside an unusual case example that illustrates the importance of increased suspicion for malignant clinical entities in this setting.
Keywords: clivus; sella; metastasis; colorectal adenocarcinoma